Handbook of families & health interdisciplinary perspectives - Crane, D. Russell; Marshall, Elaine S.; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 2006)
A broad ranging collection, as the title might suggest, the essays consider the subject from the perspectives of family studies, marriage & family therapy, nursing & family medicine gerontology, health psychology & behavioural medicine, social work & social policy.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Families -- Health and hygiene; Electronic books